Pembinaan Guru Sekolah Minggu Untuk Mengajarkan Konsep Keselamatan Pada Anak - R Riniwati (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2020)
This article discusses the formation of Sunday school teachers to teach children safety. The author uses a qualitative approach to analyze teacher needs, then the authors construct a pattern of coaching Sunday school teachers by elaborating sources of literature in accordance with the needs of teachers obtained from the needs analysis. The results of the needs analysis show there are three main needs needed by the teacher, namely aspects of knowledge about sin and salvation, aspects of personality where there are teachers who are still unsure of safety, and aspects of skills related to the ability to teach safety. The proposed pattern of coaching is to provide teaching about sin and salvation, the use of media for evangelism, mentoring or teacher supervision and evaluation.